2003
DOI: 10.1002/for.858
|View full text |Cite
|
Sign up to set email alerts
|

Non‐linear forecasts of stock returns

Abstract: Following recent non-linear extensions of the present-value model, this paper examines the out-of-sample forecast performance of two parametric and two non-parametric nonlinear models of stock returns. The parametric models include the standard regime switching and the Markov regime switching, whereas the non-parametric are the nearest-neighbour and the artificial neural network models. We focused on the US stock market using annual observations spanning the period 1872-1999. Evaluation of forecasts was based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 31 publications
0
19
0
4
Order By: Relevance
“…In another study of US listed company share prices and dividends, Kanas (2003) compares the forecasts generated by parametric standard and Markov regime switching models with the ones produced by a simultaneous (multivariate) nearest-neighbour (SNN) approach and ANNs and finds SNN to perform similarly to the others in terms of accuracy, but not as well as the Markov switching model in terms of forecast encompassing. In a recent study of short term stock price reactions to equity offering announcements, Bozos and Nikolopoulos (2011) compare forecasts by parametric, non-parametric models and expert judges and conclude that k-NN methods ranked high in terms of economic performance of the forecasts, despite their forecast accuracy being relatively lower.…”
Section: Economics and Financementioning
confidence: 99%
“…In another study of US listed company share prices and dividends, Kanas (2003) compares the forecasts generated by parametric standard and Markov regime switching models with the ones produced by a simultaneous (multivariate) nearest-neighbour (SNN) approach and ANNs and finds SNN to perform similarly to the others in terms of accuracy, but not as well as the Markov switching model in terms of forecast encompassing. In a recent study of short term stock price reactions to equity offering announcements, Bozos and Nikolopoulos (2011) compare forecasts by parametric, non-parametric models and expert judges and conclude that k-NN methods ranked high in terms of economic performance of the forecasts, despite their forecast accuracy being relatively lower.…”
Section: Economics and Financementioning
confidence: 99%
“…Hutchinson et al (1994) showed that the learning networks could be used efficiently for pricing and hedging in securities markets. Studies such as Stengos (1997, 1998), Gencay and Liu (1997), Kanas (2003), Kanas and Yannopoulos (2001), Shively (2003) and Bildirici and Ersin (2009) applied ANN models to stock market return forecasting and financial analysis. The MLP model is evaluated as an important class of neural network models.…”
Section: Neural Network: An Overviewmentioning
confidence: 99%
“…Thus, some nonlinear, nonparametric alternative approaches are proposed and adopted to estimate the time series models, the prevailing representative among them is the Artificial Neural Network (ANN). Plentiful of studies on ANN denote that ANN approach outperforms traditional MLE in forecasting financial time series and, particularly, the recurrent ANN with richer dynamic structure could capture more characteristics of data in the generalization period than the feedforward one ( (Kuan, 1995), (Wu, 1995), (Tian, Juhola & Grönfors, 1997), (Lisi & Schiavo, 1999), (Ashok & Mitra, 2002), (Gaudart, Giusiano & Huiart, 2004), (Kamruzzaman & Sarker, 2004)), but some indicate mixed or opposite results ( (Adya & Collopy, 1998); (Kanas, 2003)). While the ANN is theoretically better in estimating nonlinear finite samples without invoking a probabilistic distribution, however, it has been criticized to be vulnerable to the over-fitting problem which usually leads to a local optimum and to the empirical risk minimization, same as the MLE 1 , the latter of which results in good fit and poor forecast out-of-sample.…”
Section: Introductionmentioning
confidence: 99%